Direct methods for assessing adherence to antihypertensive therapy: witnessed intake and therapeutic drug monitoring - M. V. Ionov; I. V. Emelyanov; A. O. Konradi (Рациональная фармакотерапия в кардиологии)
Low adherence to therapy is one of the main causes of pseudo-resistant arterial hypertension (AH), associated with an increased risk of cardiovascular complications and higher direct and indirect medical costs. Adherence assessment is a crucial step in the management of patients with uncontrolled AH, particularly when therapeutic resistance is suspected. There is no "gold standard" for assessing therapy adherence. Therefore, beyond indirect methods (though simple, they are relatively unreliable), direct approaches are increasingly being utilized. These include witnessed medication intake by medical personnel — conducted alongside repeated ambulatory blood pressure monitoring using portable devices or repeated measurements by a specialist — and therapeutic drug monitoring of medications or their metabolites in biological fluids using ultra-high-performance liquid chromatography-tandem mass spectrometry. This narrative review summarizes key findings from studies on the application of these methods, outlines their respective advantages and limitations, and provides practical recommendations for their integration into everyday clinical practice. Early and simultaneous implementation of these strategies can help avoid unnecessary complex and costly diagnostic procedures in some cases and allows for more accurate identification of truly resistant AH – a patient group of scientific and clinical relevance. The use of these approaches improves the cost-effectiveness of treatment, helps uncover non-medical barriers to adherence, and strengthens the physician–patient relationship.